Polymers against Microorganisms : On the Race to Efficient Antimicrobial Materials - Rodríguez-Hernández, Juan (Springer International Publishing : Imprint: Springer, 2017)
This book provides an introductory and general overview of advances in polymers towards their employment as antimicrobial materials. The author describes current approaches for avoiding microbial contamination, toward macro-molecular antibiotics, and prevention of antibiotic-resistant bacteria by use of polymers. He establishes the remaining issues and analyzes existing methodologies for treating bacterial infections and for preparing antimicrobial materials. Offers a complete and brief overview of different strategies for preparation of antimicrobial materials; Places contamination problems in the context of what polymers can offer for remediation using different alternatives to remove and prevent bacterial infections; Describes how polymers with antimicrobial activity can interact in various ways.